Delivery, fate and physiological effect of engineered cobalt ferrite nanoparticles in barley (Hordeum vulgare L.). (February 2021) - Tombuloglu, Huseyin; Slimani, Yassine; AlShammari, Thamer Marhoon; Tombuloglu, Guzin; Almessiere, Munirah A.; Sozeri, Huseyin; Baykal, Abdulhadi; Ercan, Ismail
Abstract: Cobalt ferrite nanoparticles (CoFe2 O4 NPs) have received increasing attention in a widespread application. This work examines the fate and impact of terbium (Tb) substituted CoFe2 O4 NPs on the growth, physiological indices, and magnetic character of barley ( Hordeum vulgare L.). Sonochemically synthesized NPs were hydroponically applied on barley with changing doses (125–1000 mg/L) at germination and seedling (three weeks) stages. Results revealed a significant reduction in germination rate (∼37% at 1000 mg/L); however, a remarkable growth (∼38–65%) and biomass (∼72–133%) increase were detected at three weeks of exposure ( p < 0.05). The elements that make up the NPs ( i.e ., Tb, Co, and Fe) increased significantly in both root and leaf tissues, indicating the translocation of NPs from the root to leaf. Vibrating-sample magnetometer (VSM) analysis confirmed this finding, where magnetic signals in the root and leaf samples of the control were respectively about 26 and 75 times lower than that of NPs-treated tissues. Also, the accumulation of NPs altered the leaf photoluminescence (PL) behavior, which may have contributed to the biomass increase. Overall, Tb-doped CoFe2 O4 NPs translocate from root-to-leaf and enhance plant growth, possibly due to i) incorporation of iron within tissues, and ii) changes in photoluminescence. However, since its effects on other living things are not known yet, its agricultural use and release to nature should be considered well. Graphical abstract: Image 1 Highlights: Terbium-doped CoFe2 O4 NPs are taken up by barley and are traveled from root to leaf. The inclusion of NPs alters the photoluminescence and magnetic behavior of the leaves. The NPs are phytotoxic during germination, but surprisingly not at the seedling stage. The NPs contribute to growth and increase in biomass.